Perbandingan Hasil Belajar Biologi Menggunakan Model Pembelajaran Problem Based Learning Dan Problem Solving Kelas VII SMP Muhammadiyah 5 Surakarta Tahun Ajaran 2014 / 2015 - Ambarwati, Sri; , Dra. Aminah Asngad, M.Si (2015)
The background of the research is the teaching learning process which not effective yet and the model of learning that used has no variation. This objective of the research are comparison result of biology learning using problem based learning model and problem solving at seven grade of SMP Muhammadiyah 5 Surakarta. Collecting the sample used random sampling technique. Technique of collecting the data in this research used documentation and test. The analysis of the data used parametric test, namely One-Way ANOVA through SPSS 17.0 program. The results of average students protest used problem based learning is (75,61±4,60), higher than using problem solving learning is (72,27±6,02) and the use of conventional method is (63,78±7,08). Result of hypothesis test seen Fcount (12,361) is bigger than Ftable (3,101). Ftable Is gotten by significant importance standard 5% (df=2,87) is 0,05, so H0 refused so there found the significant difference between the third implementation of learning process in learning process based learning, problem solving, and conventional. The advanced test used Post Hoc Test, learning process in problem based learning and problem solving 0,034<0,05, learning process in problem solving and conventional 0,006<0,05, learning process in problem based learning and conventional 0,000<0,05. So it can be concluded that Ho refused and H1 accepted, it means that the model of problem based learning and problem solving there had differences toward result cognitive biology leraning at seven grade of SMP Muhammadiyah 5 Surakarta, so that the model learning process of problem based learning more effective than the model learning process of problem solving and conventional